Antidepressant-like effect of ginsenoside Rb1 on potentiating synaptic plasticity via the miR-134–mediated BDNF signaling pathway in a mouse model of chronic stress-induced depression - Guoli Wang; Tianyue An; Cong Lei; Xiaofeng Zhu; Li Yang; Lianxue Zhang; Ronghua Zhang (Journal of Ginseng Research, 2022)
Background: Brain-derived neurotrophic factor (BDNF)–tropomyosin-related kinase B (TrkB) plays a critical role in the pathogenesis of depression by modulating synaptic structural remodeling and functional transmission. Previously, we have demonstrated that the ginsenoside Rb1 (Rb1) presents a novel antidepressant-like effect via BDNF–TrkB signaling in the hippocampus of chronic unpredictable mild stress (CUMS)-exposed mice. However, the underlying mechanism through which Rb1 counteracts stress-induced aberrant hippocampal synaptic plasticity via BDNF–TrkB signaling remains elusive. Methods: We focused on hippocampal microRNAs (miRNAs) that could directly bind to BDNF and are regulated by Rb1 to explore the possible synaptic plasticity-dependent mechanism of Rb1, which affords protection against CUMS-induced depression-like effects. Results: Herein, we observed that brain-specific miRNA-134 (miR-134) could directly bind to BDNF 3′UTR and was markedly downregulated by Rb1 in the hippocampus of CUMS-exposed mice. Furthermore, the hippocampus–targeted miR-134 overexpression substantially blocked the antidepressant-like effects of Rb1 during behavioral tests, attenuating the effects on neuronal nuclei-immunoreactive neurons, the density of dendritic spines, synaptic ultrastructure, long-term potentiation, and expression of synapse-associated proteins and BDNF–TrkB signaling proteins in the hippocampus of CUMS-exposed mice. Conclusion: These data provide strong evidence that Rb1 rescued CUMS-induced depression-like effects by modulating hippocampal synaptic plasticity via the miR-134-mediated BDNF signaling pathway.